P-C20 Th17, CCR6+ cells lack RNAses and are highly permissive to HIV infection: Implications for pathogenesis and therapy. (March 2017) - Lafferty, Mark K.; Christensen-Quick, Aaron; Sun, Lingling; Garzino-Demo, Alfredo
Abstract : Th17 cells (i.e., IL17-producing T cells) are selectively depleted in acute HIV infection and in pathogenic, but not in non-pathogenic, SIV infection. Since IL17 stimulates the production of antimicrobial peptides including defensins and contributes to the preservation of mucosal integrity, Th17 cell loss initiates a vicious cycle of increased mucosal permeability, microbial translocation, and inflammation that further fuels HIV infection and immune activation, contributing to HIV pathogenesis. Our studies demonstrate that Th17 cells are more permissive to HIV infection than non-IL17 secreting cells. Compared to activated, IFN-γ secreting T cells, Th17 cells are more likely to get infected and express higher levels of HIV p24, even when HIV pseudotyped with AMLV envelope is used to infect cells, indicating that the increase in infection is not due to variations in HIV receptor expression. CCR6, a chemokine receptor expressed on Th17, cells further defines a subset of activated cells that is highly susceptible to HIV infection. Using RNA microarray technology, we determined that Th0 CCR6-cells express higher levels of RNASEs 2, 3 and 6 than Th17 CCR6+ cells. We also found that these RNASEs were more effective in inhibiting HIV in Th17 than Th0 cells, indicating that they may play a key role in reducing infection in Th0 cells. These findings point at future directions for prevention and treatment of HIV infection. First, since we characterized that beta-defensin 2 inhibits HIV infection in CCR6+ cells bi inducing expression of APOBEC3G, the defensin itself or small molecule derivatives could be used to prevent loss of Th17 cells that express CCR6. Second, the elucidation of the mechanism of activity of RNASEs could help protecting highly permissive TH17 cells. Third, pathways leading to T cell activation and Th17 differentiation could be targeted to decrease cells permissivity and lower immune activation.